Fungal immunization potentiates CD4+ T cell-independent cDC2 responses for cross-presentation - Kulkarni, Nitish A.; Nanjappa, Som G. (Frontiers in Immunology, 2025)
The incidence rates of fungal infections are increasing, especially in immunocompromised individuals without an FDA-approved vaccine. Accumulating evidence suggests that T cells are instrumental in providing fungal immunity. An apt stimulation and responses of dendritic cells are pivotal in inducing T-cell responses and vaccine success. Using a mouse model of fungal vaccination, we explored the dynamics, kinetics, activation, and antigen presentation of dendritic cell subsets to unravel the features of dendritic cell responses in the absence of CD4+ T cell help. The subcutaneous fungal vaccination induced more robust cDC2 responses than the cDC1 subset in draining lymph nodes. A single immunization with Blastomyces yeasts bolstered DC responses that peaked around day 5 before reverting to basal levels by day 15. The migratory cDC2 was the dominant DC subset, with higher numbers than all other DC subsets combined. Fungal vaccination augmented costimulatory molecules CD80 and CD86 without altering the levels of MHC molecules. Despite the higher fungal antigen uptake with migratory cDC2, the mean cross-presentation ability of all DC subsets was similar. Counterintuitively, deleting CD4+ T cells enhanced the DC responses, and CD4+ T cells were dispensable for conventional cross-presenting cDC1 responses. Collectively, our study shows that fungal vaccination selectively augmented cDC2 responses, and CD4+ T cells were dispensable for DC activation, antigen uptake, expression of costimulatory molecules, and cross-presentation. Our study provides novel insights into DC responses to an effective fungal vaccine for designing efficacious vaccines tailored for immunocompromised hosts.